Coercive Isomorphism in Bureaucratic Reform in Tanimbar Islands Regency - Muriany, Telly; Sanjak Ruhunlela, Victor (CV. Inara, 2024)
The Tanimbar Islands Regency has several contradictions with the idea of bureaucratic reform designed by the state, leading to coercive isomorphism in organizational changes due to external pressures. This study employs a qualitative approach with a case study method, gathering data through interviews and document studies. The results indicate that: first, institutional reform will only succeed if there is fairness in resource distribution, both in budget and infrastructure, and if political intervention is minimized to enhance the independence of the existing structures, both regional and functional. This independence can only be achieved by strengthening the capacity of the apparatus in structured performance management based on measurable goal achievements. Second, governance system improvements will not be effective without reforming the mentality of the officials, as improving mentality can maximize compliance with policies and procedures, reducing compromises and formalities in the bureaucracy. Third, in a coercive environment, local governments adjust the qualifications of officials merely to meet the demands of professional image and formality. Fourth, an orientation towards practical politics affects the non-simultaneous bureaucratic reform process and hinders inter-agency coordination.